Sustainability from the business model to the communities (2021)
This chapter discusses the bases that guarantee the best performance of any corporate management system, especially the strategies on culture and organizational design, and leadership that supports the supervision and commitment of employees at the production plant level to promote sustainable development. For this purpose, the best practices that contribute to maximum participation and decisive attitude at the time of undertaking any change are explained